PEMANFAATAN BATU KARANG-PASIR DALAM PROSES PENGOLAHAN GREYWATER - Weking, Maria Y. T.; Tawa, Bibiana D.; Ledoh, Sherlly M. F.; Gauru, Imanuel (Chemistry Notes, 2018)
A study of Greywater treatment has been conducted. By utilising vast local coral reefs and sand as filter media, we aimed to treat synthetic waste water in term of reducing its pH, temperature, COD, phosphates and turbidity parameter. The sample was passed gravitationally through 3 variation of filtering agent composition i.e. 1:1, 2:1 and 1:2 of coral reefs to sand ratio respectively in 2 flow rates: 0,4 and 0,8 mL/s. The collected up flow effluent was then analysed. Data resulted were then tested with ANOVA statistical test. The result showed that the mass ratio of the media and the flow rate influenced parameters. The best treatment was obtained at the 1:1 mass ratio in 0,4 mL/s flow rate. The effluent fulfilled the Indonesian water standard quality according to PP No 82 tahun 2001 and PERMENKES No 416/MENKES/PER/1990.